Empowering Persons with Disabilities in the Fashion Industry: A Case Study of Layak Indonesia’s Inclusive Branding Strategy - Siagian, Ade Indriani; Lisnarini, Naurah; Rizkiana, Maudy (Universitas Ahmad Dahlan, 2025)
The fashion industry often relies on tokenism or “pity narratives” when representing persons with disabilities, which limits their potential and perpetuates marginalization. This qualitative study addresses this critical gap by analyzing the strategy of Layak Indonesia, a local fashion brand that places the empowerment of persons with disabilities at the core of its mission, thereby challenging conventional industry norms. This research contributes by offering an empirical model of authentic and holistic inclusive branding within the Southeast Asian context, moving beyond purely theoretical discussions of social justice and woke-washing. Guided by a constructivist paradigm and employing a case study approach, data were collected through in-depth interviews with the founder and talents of Layak Indonesia, complemented by observational analysis of documents and media narratives. Data analysis utilized Categorical Aggregation, as proposed by Stake, which involves the systematic collection of events to interpret and construct meaning. The findings reveal that Layak Indonesia implements a holistic and structural strategy by prioritizing persons with disabilities as operational staff and creative partners, while explicitly rejecting the inspiration porn narrative. This approach effectively reframes disability identity in the public sphere, transforming individuals from objects of sympathy into professional, creative, and empowered subjects. As a result, the strategy contributes to increased self-confidence and expanded career opportunities for persons with disabilities. However, the study also identifies a significant “say–do gap” among consumers, wherein high levels of brand awareness and moral support do not consistently translate into purchasing behavior, largely due to price sensitivity and competition related to product quality. In conclusion, Layak Indonesia’s model provides a robust framework for authentic brand activism. Nevertheless, its long-term sustainability depends on the ability to balance strong social values with competitive business strategies within the highly demanding fashion market.